Exposure to second-hand smoke in the context of tobacco policy changes in Estonia, 1996–2016. (8th March 2019) - Reile, Rainer; Pärna, Kersti
Abstract: Background: Exposure to second-hand smoke (SHS) is a preventable cause of disease and disability that can effectively be tackled by tobacco legislation. The aim of the study was to analyse the trends of SHS exposure and its sociodemographic patterning during 1996–2016 in the context of tobacco policy changes in Estonia. Methods: Nationally representative data from biennial health surveys in 1996–2016 ( n = 14 629) were used to present prevalence ratios for SHS exposure among non-smokers in Estonia. Joinpoint regression and multivariable logistic regression were used to study the sociodemographic and socio-economic differences in SHS exposure and its changes during the period. Results: Exposure to SHS among non-smoking men and women has declined 3.6 and 5 times, respectively, during 1996–2016. While the rate of change was constant among men throughout the period, the decline in SHS exposure among women became significantly faster after 2006 compared with the previous period. However, 15.6% [95% confidence interval (CI) 13.1–18.3%] of men and 8.8% (95% CI 7.1–10.6%) of women were still exposed to SHS in 2016 with higher odds found for younger age groups, non-Estonians and those with lower education and income. Conclusions: The consistently declining prevalence of SHS exposure among non-smoking population can be at least partially attributed to implementation of tobacco legislations in 2000s. However, the existing sociodemographic and socio-economic differences in SHS exposure require further attention as those in more vulnerable positions are also more exposed to SHS-related health harms.